Рим как исторический и фикциональный топос в повести Андрея Гуляшки „Похищение Данаи“ - Няголова, Наталия (SlavVaria, 2026)
Rome as a historical and fictional topos in Andrey Gulyashki’s short novel The Stealing of Danae. The article presents observations on the functioning of the topos “Rome” in Andrey Gulyashki’s short novel The Stealing of Danae (1978). The short novel is part of the cycle The Adventures of Avakum Zahov, which is dedicated to the investigations of a Bulgarian detective and counterintelligence officer – a quite rarely seen in socialist realism literature character. In the work the topos of Rome demonstrates a number of features that deviate from the real geography of the city as to correspond with certain ideological messages, which are typical for socialist realism aesthetics. The following text also traces the connection with the topography of Italian films of the “poliziesco” genre, which was very popular in the 1970s in Italy and in the countries of the former socialist bloc.